Peningkatan Edukasi Pengetahuan UMKM Bakpia Pathok 731 Dewa Dalam Identifikasi Ancaman dan Pengendalian Siklus Bisnis - Wardhani, Aurelia Melinda Nisita (Manaruko: Jurnal Pengabdian Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a type of business that contributes to the economy in Indonesia. This knowledge-increasing educational activity is important to do in order to add insight into the importance of the role of internal control in the income cycle at UMKM "Bakpia Pathok 731 Dewa". The method used in carrying out this activity is the preparation, observation, implementation, and evaluation stages. The results of this activity are capable identifying threats and proposing evidence of transactions in the form of serial numbered note numbers as a first step in implementing internal control. In addition, this MSME accepts this proof of transaction proposal to be implemented in their organization in the future.